Model of Risk Behavior for Prevention of HIV/AIDS Transmission Based on Self-Efficacy in Adolescents - Permatasari, Dian; Mulyadi, Eko; Gamar Dian Pratiwi, Iva; Indriyani, Ratna; Puspitasari, Dian Ika (Journal of Applied Nursing and Health, 2024)
Background: Adolescents are a group that is vulnerable to the spread of HIV/AIDS due to risky behavior such as unprotected sexual intercourse and drug use. One approach that can be used to understand and reduce this risky behavior is self-efficacy, which is an individual's belief in their ability to take preventive action. The purpose of this study was to test the model of risky behavior towards preventing HIV/AIDS transmission based on self-efficacy in adolescents in Sumenep City District, Methods: This study is an observational analytical study, the population of the study is all adolescents aged at least 16 years in the Sumenep City District Results: Based on the Goodness of Fit table, the final model for adolescent risk behavior in the Sumenep City District can be said to be fit when viewed from several criteria, for example the Chi-square value of 0.001 (which is expected to be small), the GFI value of 0.915 (standard> 0.90), the NFI value of 0.934 (standard> 0.90), and the RMR value of 0.030 (standard <0.05). Conclusion: Based on the results of the study, it can be concluded that the self-efficacy-based behavioral model is effective in reducing risky behavior and increasing preventive measures for HIV/AIDS transmission among adolescents in the Sumenep City District. This approach can be an effective strategy in preventing HIV/AIDS in the adolescent community by increasing their confidence in their ability to take appropriate preventive measures.